Social Media and Foreign University Collaboration: A Multi‐Perspective Descriptive Analysis for Indonesian Private Universities - Junaid Ali Saeed Rana (Business and Entrepreneurial Review, 2020)
The importance of social media for universities is an important tool for marketing purposes by adopting aggressive marketing strategies. The existence of foreign-based Higher Education Institutes (HEI) in Indonesia is almost non-existent. The government of Indonesia through education ministry requires any foreign HEIs that will operate in Indonesia to have a formal collaboration with the government accredited Indonesian HEIs. The paper empirically studies the multiple-perspective (management role and students’ role) descriptive approach in evaluating the social media usage and the importance of foreign university collaboration. The data collected from 34 universities (management perspective) and from the 5 most populated universities (for student perspective). The data analyzed and compared using graphs to draw some meaningful conclusions. The paper concludes with empirical findings based conclusions to managers to effectively using social media to its optimum benefit and gaining potential assistance from foreign university collaboration. Some meaningful suggestions to the management as how strategically social media should be managed.